2017
DOI: 10.1017/s1049023x16001515
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake-Related Orthopedic Injuries in Adult Population: A Systematic Review

Abstract: The searches identified 4,704 articles: 4,445 after duplicates were removed. The papers were screened for title and abstract and 65 out of those were selected for full-text analysis. The quality of data does not permit a standard-of-care (SOC) to be defined. Scarcity and poor quality of the data collected also may suggest a low level of accountability of the activity of the international hospital teams. Qualitatively, it is possible to define that there are more open fractures during daytime hours than at nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
2
34
0
1
Order By: Relevance
“…Most studies of earthquake impacts have focused on short-term consequences like mortality [ 30 ] or injury [ 31 , 32 ]. However, there is a small but growing body of evidence studying the effects of earthquakes on nutrition, derived largely from South American contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of earthquake impacts have focused on short-term consequences like mortality [ 30 ] or injury [ 31 , 32 ]. However, there is a small but growing body of evidence studying the effects of earthquakes on nutrition, derived largely from South American contexts.…”
Section: Discussionmentioning
confidence: 99%
“…One reason may be the lack of a common definition of what is an injury. High-magnitude earthquakes might cause more crush injuries and burying than low magnitude [ 35 •]. Building damage is a major cause of death and injury in earthquakes, especially where solid building materials such as concrete are used, and buildings are not adapted to withstand ground motion [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Spinal column fractures accounted for 17% of the total injuries, and more than 4% of these were spinal injuries, while 10% of fractures involved the pelvic ring. They also found that fracture incidence seemed to correlate with the Richter Magnitude Scale, with a high-energy earthquake causing more fractures [ 35 •].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When it is possible, conservative treatment for fractures should be encouraged at disaster site. [26][27][28] Neurosurgical injuries demand correct triage procedures and prompt intervention with appropriate and qualified equipment. This will play a key role in reducing morbidity and mortality.…”
Section: S20mentioning
confidence: 99%